Analysis of The Level of Understanding of Class X Students' Concepts on The Periodic Table of Elements Material Assisted by The Three-Tier Multiple Choice Test Instrument - Damayanti, Yosephine Debbie; Wulanningtyas, Melania Eva (Universitas Negeri Semarang, 2024)
Chemistry is one of the subjects that is abstract and emphasizes concepts. This is often the cause of low levels of student understanding (misconceptions). Not only because of inappropriate learning methods or models, but less in-depth question instruments also increase students' misconceptions. This study was conducted with the aim of analyzing the level of conceptual understanding of grade X students on the Periodic System of Elements (SPU) material which is basic material before other complex chemical materials. Misconception analysis was carried out using Rasch analysis from the results of the Three-Tier Multiple Choice Test (TTMCT) instrument. The method used is a quantitative method and expert validation was carried out by eight experts. The study was conducted in 5 schools (public-private). The results of the study showed that students' conceptual understanding was low and several misconceptions were found.